1987
DOI: 10.1084/jem.165.6.1719
|View full text |Cite
|
Sign up to set email alerts
|

Human autoantibodies against a desmosomal protein complex with a calcium-sensitive epitope are characteristic of pemphigus foliaceus patients.

Abstract: Pemphigus foliaceus (PF) patients have antibodies against a tightly, but noncovalently bound complex of polypeptides, which consists of desmoglein I (DGI) and other, possibly desmosomal, proteins. Most PF antibodies bind a calcium-sensitive epitope on this complex and chelation of calcium destroys the reactivity of these sera with the complex, but not the complex itself. The PF sera that do bind the desmosomal complex in the absence of calcium are those sera capable of binding denatured DGI on immunoblotting, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
2

Year Published

1988
1988
1992
1992

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 148 publications
(73 citation statements)
references
References 10 publications
2
69
0
2
Order By: Relevance
“…These data indicate that some PV sera, in addition to having antibodies to the PV complex, have antibodies to a calcium-sensitive epitope on the PF complex. Similarly, we have previously shown that most PF sera also bind a calciumsensitive epitope on the PF complex (2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These data indicate that some PV sera, in addition to having antibodies to the PV complex, have antibodies to a calcium-sensitive epitope on the PF complex. Similarly, we have previously shown that most PF sera also bind a calciumsensitive epitope on the PF complex (2).…”
Section: Resultsmentioning
confidence: 99%
“…Immunoprecipitations were performed as previously described (2,8,9,12) except that in most experiments 2 mM CaCl2 was added to all buffers and washing solutions. Approximately 20 X 106 cpm of 251I-labeled epidermal extracts or 4 X 106 cpm of '4C-labeled cultured keratinocyte extracts and 10-15 Al of sera were used per immunoprecipitation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Disease control sera were obtained from patients with clinically and histologically typical pemphigus foliaceus (PF). PF is an autoimmune blistering disease of epidermis, in which autoantibodies bind DGI (26)(27)(28). These PF control sera showed characteristic immunofluorescence findings.…”
Section: Methodsmentioning
confidence: 99%